2023
DOI: 10.1093/scan/nsad038
|View full text |Cite
|
Sign up to set email alerts
|

Midfrontal theta as an index of conflict strength in approach–approach vs avoidance–avoidance conflicts

Abstract: The seminal theory of motivational conflicts distinguishes between Approach-Approach conflicts, in which a decision is made between desirable alternatives, and Avoidance-Avoidance conflicts, in which a decision is made between undesirable alternatives. The behavioral differences between Approach-Approach and Avoidance-Avoidance conflicts are well documented: both Lewin’s and Miller’s original conceptualization, as well as abundant empirical research that followed, showed that Avoidance-Avoidance conflicts are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…In Study 1, we first replicated findings from previous research (Atthowe, 1960;Barker, 1942;Boyd et al, 2011;Enisman & Kleiman, 2024;Epstein & Smith, 1967;Heitmann & Deutsch, 2019;Houston et al, 1991;Levy et al, 2023;Minor et al, 1968;Murray, 1975;Ringuette, 1965;Schill, 1966;Terry, 2010), showing that AV-AV conflicts take longer to resolve than AP-AP conflicts. We additionally showed that AP-AP and AV-AV conflicts were distinguishable using mouse-tracking measures of conflict-strength (AUC and MD).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In Study 1, we first replicated findings from previous research (Atthowe, 1960;Barker, 1942;Boyd et al, 2011;Enisman & Kleiman, 2024;Epstein & Smith, 1967;Heitmann & Deutsch, 2019;Houston et al, 1991;Levy et al, 2023;Minor et al, 1968;Murray, 1975;Ringuette, 1965;Schill, 1966;Terry, 2010), showing that AV-AV conflicts take longer to resolve than AP-AP conflicts. We additionally showed that AP-AP and AV-AV conflicts were distinguishable using mouse-tracking measures of conflict-strength (AUC and MD).…”
Section: Discussionsupporting
confidence: 78%
“…We did not test the measures' reliability but relied on vast previous literature (Arkoff, 1957;Atthowe, 1960;Barker, 1946;Boyd et al, 2011;Chernev, 2004;Dhar & Sherman, 1996;Enisman & Kleiman, 2024;Epstein & Smith, 1967;Heitmann & Deutsch, 2019;Houston et al, 1991;Hovland & Sears, 1938;Levy et al, 2023;Minor et al, 1968;Murray, 1975;Ringuette, 1965;Schill, 1966;Smith & Gehl, 1974;Terry, 2010). If covariates are used, have the researchers ensured they are not affected by the experimental manipulation before including them in comparisons across experimental groups?…”
Section: Statistical Validitymentioning
confidence: 99%
See 3 more Smart Citations